Malpraktek Paramedik - I Nyoman Kantun (Jurnal Ilmiah Raad Kertha, 2018)
Hearing a doctor's view of the public is a very highly prespesional person in his field, and he is very honorable even it seems there is no mistake that enveloped him, along with the development of the population and accompanied by technological progress so rapidly that raises various demands of a very complex interest in community life and state, as well as inevitable various problems related to public health, which are generally undertaken by medics / doctors.Efforts to anticipate the problem has been done with the support of advancement in the world of doctors, but the medical error in the field of medicine apparently requires a legal tool to protect patients from the actions of the medic, so doctors are not spared from the legal entrapment of kelalainnya in carrying out his profession, which is often called malpractice.Thus, in a state of law no one escapes the law, all citizens of society without exception to violate the law in accordance with law trap in accordance with the error / encyclopedia. The physician's diligence in practicing his profession is also not escaped from the bondage of law, it is of course intended to protect patients from the abuse of medic / doctors, who once seemed to be medics / doctors untouched by law.